Islamophobia in S. K. Ali's Love from A to Z - Khikmatus Shoumi (LITERA KULTURA : Journal of Literary and Cultural Studies, 2021)
Islamophobia has been a common issue in today’s discourse. It is a negative attitude towards Islam that possibly leads to discrimination or other violent actions against Muslims based on a feeling of hatred, fear, or superiority over Muslims as a minority group. Islamophobia is not only able to be found in real life but also is occasionally represented through fictional works, especially a novel. This study aims to describe how Islamophobia is portrayed in S. K. Ali’s Love from A to Z using the concept of Islamophobia as cultural racism and to reveal how Zayneb, as the victim of Islamophobia, responds to Islamophobia using a minority identity development model by Atkinson et al. Islamophobia as a form of cultural racism is portrayed by presenting Muslim attire issue, anti-Arab issue, and disdaining value of Islam. In response to Islamophobia, Zayneb develops stages of minority identity by self-deprecating, becoming aware and upset about Islamophobia, standing up, and involving in a movement to fight back against Islamophobia. Keywords: cultural racism, Islamophobia, minority, Muslims